Stepwise Evaluation of Information Systems in an University Hospital - Bürkle, T.; Kuch, R.; Prokosch, H.-U.; Dudeck, J. (Methods of Information in Medicine, 1999)
A prospective intervention study with historical control has been performed at Giessen University Hospital, Germany, to investigate the influence of electronic data processing systems on nurses’ working environment. Two wards of the medical department were selected for this study, using the combined approach of work-sampling methods and questionnaires. In the first intervention a central information system with restricted functions was introduced. For the second intervention an additional nursing information system was installed. The distribution of nurses’ worktime into the fields of general nursing care, specific nursing care and administrative activities was not influenced by electronic data processing. No time saving could be measured. Results of the questionnaires did, however, indicate a positive influence of the hospital information system on nurses’ working environment.
Keywords: Evaluation; Nursing Information System; Hospital Information System